Monitoring and Evaluation to Improve School Quality - Gustiani, Frisca; Barus, Inneda Citra; Elfrianto, Elfrianto (Indonesian Journal Education, 2023)
Good school quality is created from the results of evaluation and monitoring, so the school must carry out an evaluation in creating a better goal, this is done so that the learning process can run well and correctly. This literature review aims to analyze the implementation of monitoring and evaluation of school quality. The results of monev consist of data about various information such as the state of curriculum implementation, teacher performance, student performance, and so on. This data is used as material for improving and refining the program so that it is hoped that student learning outcomes will improve. Student achievement and other data are used as a basis for program improvement, with the goal of increasing the anticipated level of educational quality